FORMULATION AND EVALUATION OF HERBAL LOZENGES FOR MOUTH ULCERS (International Journal of Food and Nutritional Sciences, 2022)
This study introduces the development and evaluation of herbal lozenges designed specifically for treating mouth ulcers, featuring Neem (Azadirachta indica) and Tulsi (Ocimum sanctum L) as key ingredients. Neem is well known for its diverse therapeutic compounds, providing strong anti-inflammatory, antimicrobial, and wound-healing properties. Tulsi, revered in traditional medicine for its anti-inflammatory and analgesic effects, complements Neem by enhancing its healing characteristics. The lozenges are formulated to dissolve slowly in the mouth, ensuring prolonged contact with ulcerated oral tissues to relieve pain and promote healing. The synergistic blend of Neem and Tulsi offers a promising natural approach to managing mouth ulcers, effectively addressing symptoms while supporting overall oral health and well-being.